(untitled) (Ahkam: Jurnal Hukum Islam, 2022)
The level of spread of the Covid-19 and the resulting death encourages various community activities to be able to adapt to the situation and regulations as a preventive measure. Religious activities that often bring mass gatherings are one of the activities that are affected, especially worship activities. The worship activities, especially those that make congregation an important part of it, such as fardu and Friday prayers, are required to adapt as a form of soul preservation which is one of the main objectives (maqāṣid) of Islamic law. On the other hand, the law of worship is basically ta’abbudī and tawqīfī whose space for ijtihad is narrow. The adaptations made have the potential to lead to heresy. This study tries to examine the possibilities of these adaptations and the extent to which these possibilities are carried out. The approach taken is a qualitative approach to literature through the theory of maqāṣid al-sharī’ah especially to investigate potential contradictions between the preservation of religion and the soul. This study pays attention to the rules governing the structure, level and type of maqāṣid with a case study on the adaptations in Friday prayer. The phenomena discussed include the suspension of prayers, arrangement of rows, and the synchronous practice. This study concludes that an adaptive form that is able to preserve of all maqāṣid kullīyah without sacrificing one of them should be done wherever possible. When this is not possible, the intermediate tarjih must consider various aspects of each prevailing condition through maqāṣid perspective.